Migrant infrastructure: Transaction economies in Birmingham and Leicester, UK. (May 2017) - Hall, Suzanne; King, Julia; Finlay, Robin
Infrastructure convenes social relations, thereby revealing how city dwellers access shared resources in the context of growing inequality. Our exploration of migrant infrastructure engages with how highly variegated migrant groups develop a 'transaction economy' (Simone, 2004) within marginalised city streets, exchanging goods and services, and information and care. In the context of ethnically diverse and deprived urban places, where state resources are increasingly diminished, we explore how a precarious yet skilled resourcefulness emerges through the street. Our empirical exploration of migrant infrastructure is located on Rookery Road in Birmingham and on Narborough Road in Leicester, and draws on qualitative surveys with 195 self-employed proprietors from many countries of origin. The streets reveal transaction economies that intersect local and migratory resources, eluding the categorisation of cities associated with either a global North or a global South. Further, the lively nature of street transactions decentres western-centric measures of economic value. From the street, we develop a postcolonial analysis of infrastructure that relates properties of historic depth (power), socio-spatial texture (materiality) and locality (place).